Understanding of Report Card Quality and Principal's Leadership Regarding Preparation of School Work Plans in Public Elementary Schools West Pasaman Regency - Yahya Yahya; Jupriani Jupriani; Wulandari Wulandari (Green Publisher Indonesia, 2023)
This research is motivated by the ability of school principals who are less able to prepare School Work Plans and are less able to utilize the results of Quality Reports in making School Work Plans so that there is no synchronization between Quality Reports and School Work Plans. This study aims to determine the contribution of understanding the quality report cards and the principal's leadership to preparing school work plans in public elementary schools (SD) of West Pasaman Regency. This study uses the Proportional Stratified Random Sampling, with a population of 252 principals and a sample of 82 people from the total population taken from the principal at the State Elementary School in West Pasaman Regency. The type of data used is primary data. Sources of data come from the number of principals, characteristics, and so on. The analysis technique used is the average score (Mean) for the description of the data, the requirements test, namely the normality test, homogeneity test, linearity test, and independence test. Then test the hypothesis with simple linear regression and multiple linear regression. The results of the study stated that the understanding of the quality report card and the principal's leadership together contributed to the preparation of the school work plan by 34.3%, this explains that the better understanding of the quality report card and the leadership of the principal has an impact on the better quality of the preparation of school work plans.